Instrumentos de financiamiento urbano en la Ley de Desarrollo Urbano Sostenible - Lau Gastelo, Erick (2025)
With the enactment of the Sustainable Urban Development Law, Law No. 31313, a series of instruments were introduced that enable local governments to increase the resources available to them for financing urban development within their respective jurisdictions, based on the very exploitation of urban land.In this article, we aim to examine these instruments; however, we begin by analyzing the context and objectives of the aforementioned Sustainable Urban Development Law, in order to understand the role that urban financing instruments play within the framework of the new paradigm for urban land planning and management proposed by the Law.